TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP MUTU PEMBELAJARAN DI SEKOLAH DASAR - ARFANSYAH ARFANSYAH (GURUKU, 2022)
This is asking about points to see how far the need for information and communication technology in learning, especially elementary school (SD). The use of information and communication technology in learning in this paper is encouraged to be limited to learning preparation. Teachers can use information and communication technology to prepare learning guides and/or when learning preparation takes place. With information and communication technology, teachers can enter educational materials and find references around learning strategies that are suitable for their students. In learning the instructor can deliver material that is more effectively known by students with the help of the use of information and communication technology. The application of information and communication technology is also not as directly connected but must also look at the characteristics of students. Then the preparation of learning will be quality and important with the use of information and communication technology in accordance with this